Transcriptomics Analyses Reveal Wheat Responses to Drought Stress during Reproductive Stages under Field Conditions - Ma, Jun; Li, Ruiqi; Wang, Hongguang; Li, Dongxiao; Wang, Xingyi; Zhang, Yuechen; Zhen, Wenchao; Duan, Huijun; Yan, Guijun; Li, Yanming (Frontiers in Plant Science, 2017)
Drought is one of the common abiotic stresses that limit wheat production worldwide. To ensure food security for the rapidly increasing world populations, improving wheat yield under drought stress is urgent and relevant. In this study, a RNA-seq analysis was conducted to study the effects of drought on wheat transcriptome changes during reproductive stages under field conditions. Our results indicated that drought stress during early reproductive periods had a more severe impact on wheat development, gene expression and yield compared with drought around flowering periods. In total, 115,656 wheat genes were detected, including 309 differentially expressed genes (DEG) responded to drought at different developmental stages. Validation of DEGs through RT-qPCR indicated that the transcriptome changes obtained by RNA-Seq were accurate in this study. GO analysis suggested that the DEG genes involved in many important processes under drought stress during wheat development, such as the floral development, photosynthesis activities and stoma movements etc. The subcellular location of proteins of the DEGs showed they were mainly located at nucleus, peroxisome, mitochondria, plasma membrane and chloroplast, respectively, indicating these organelles played critical role in drought stress in wheat at early developmental stages. Furthermore, we selected five DEGs and confirmed their responsiveness to drought under different genetic backgrounds. Functional verification of these DEGs will be performed in our subsequent research. Collectively, these results advance our understanding of the transcriptome changes under drought stress on wheat at early reproductive stages, which will be useful targets to manipulate drought tolerant at different development stages during wheat growth.